Potential study of retention Ponds in the Samudra University environment to meet raw water needs and control floods - Irwansyah, Irwansyah; Isma, Faiz; Fajri, Haikal; Basrin, Defry (Faculty of Geography, Universitas Gadjah Mada, 2024)
This study aims to evaluate the potential locations and volume capacities of retention ponds at Universitas Samudra (Unsam) to reduce flood discharge, provide raw water supply, and ensure water quality. The research supports the concept of a smart and green campus at Unsam. Water availability was calculated using the FJ Mock model, while water demand was projected based on the number of users. The retention pond capacity for flood control and raw water availability was assessed using the HEC HMS model. Water quality testing, including physical, chemical, and biological parameters, was conducted at the BTKLPP Class I Medan laboratory. The results indicate that the water demand at Unsam is 3 m³/day, which can be met by the reliable discharge of 16,344.93 m³/day. The existing reservoir retention pond, with a volume of 509,788.80 m³, contributes to flood discharge reduction; however, its water quality does not meet raw water standards, particularly due to high concentrations of Total Coliform and Escherichia Coli. Meanwhile, the Cotkala-Unsam retention pond can provide 103,596.96 m³ of water with quality that meets acceptable limits.